A Revisit Motion Analysis of Lifting Fresh Fruit Bunches during Oil Palm Harvesting - Josephine Ling Laing (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To conduct and enumerate the time motions of workers at three different lifting activities. To examine the energy and power consumption during lifting of the fresh fruit bunches of the respective activities. To analyse and evaluate the relationship between the workers and the lifting activity.